Natural selection and context-dependent values - Houston, A. I. (1997)
A simple model in which an animal makes a choice between two simultaneously available foraging options is used to show that we cannot expect natural selection to assign an absolute value (based on fitness) to each option. The example shows that the value of an option depends on its context; in particular, it depends on the option with which it is paired. This dependence results in a pattern of choice that violates a stochastic form of transitivity.